Transformação de cicloexano e metilcicloexano sobre as zeólitas HMCM-22, HZSM-5 e HUSY rendimento e seletividade a hidrocarbonetos leves - Scherer, Ediane Karine (2009)
In Brazil, the oil production with high naphthenic hydrocarbon (HC) content and the hard growing for the petrochemical market have led to the necessity to maximize the production of light HC (in special light olefins). The new technologies must involve the use of acid catalysts that have high activity and selectivity. In despite of the naphthenic HC make part of the feed of the FCC reactor, few studies have been devoted to their transformations on HUSY and HZSM-5 zeolites, main active components of the FCC catalysts, and also on the MCM-22 zeolite. In this context, the objective of this work was to evaluate the cyclohexane and methylcyclohexane transformations on the above mentioned zeolites. The MCM-22 was hydrothermally synthesized under static conditions and in the case of USY and ZSM-5 zeolites, commercial samples were used. The samples were characterized by thermogravimetric analysis, X ray diffraction, chemical analysis, nitrogen sorption, scanning electron microscopy, and evaluated in the cyclohexane and methylcyclohexane transformation at 400 oC, with after carbon analysis. The studied zeolites were active in the studied reactions, nevertheless, the conversion, yield and selectivity to light HC were dependent on the zeolite structure, number and strength of the acid sites and the external area. The HUSY zeolite, due to their higher aluminum content, showed higher activity with high yield to isomerization products. On the contrary, on the HZSM-5 zeolite the cracking products were favored with high selectivity to propane and butane. On the base of their structural and textural properties, the HMCM-22 zeolite showed a mixture of cracking and isomerization products. The selectivity to light olefins (C2=, C3= and C4=) was higher on the HZSM-5 zeolite, in which the bimolecular reactions of hydrogen transference were not favored due to the steric restrictions imposed by their microporous, which are smaller in diameter. The microporous structure was determinant in the zeolite deactivation by coke formation.